POLA PENYELESAIAN TANAH ANTARA MASYARAKAT DI DAERAH GILI TRAWANGAN DENGAN PT. WANAWISATA ALAM HAYATI (STUDY KASUS DI GILI TRAWANGAN KABUPATEN LOMBOK UTARA) - DIANI, NI WAYAN SRI (GANEC SWARA, 2018)
This study aims to: 1) analyze the control of legal land ownershi by PT. Natural Biological Wanawisata, 2) analyze what factors behind the occurrence of disputes between PT. WAH with the community in Gili Trawangan area, and 3) to recognize and analyze the efforts taken by the parties and the legal solutions used in dispute settlement. The type of research used is empirical normative, using approach method by using approach of legislation, case, conceptual, history, and comparative approach. The results of this research are: in the dispute over land ownership rights by Gili Trawangan residents, local government is more favorable to investors who have business license and building rights certificate. Factors that become problems include the absence of firmness from the Regional Government of North Lombok Regency and lack of coordination by BPN. Dispute resolution mechanisms in this way are classified in non-litigation media as a concept of conflict resolution or cooperative dispute